2004
DOI: 10.1111/j.1365-2044.2004.03833.x
|View full text |Cite|
|
Sign up to set email alerts
|

Retracted: Reversal of vecuronium with neostigmine in patients with diabetes mellitus

Abstract: SummaryReversal of vecuronium-induced neuromuscular blockade with neostigmine was compared in two groups of 16 subjects: patients with Type 2 diabetes mellitus and normal controls. When the first twitch of the train-of-four had returned to 25% of the control value, neostigmine 40 lg.kg )1 and atropine 20 lg.kg )1 were given to reverse the neuromuscular blockade. The train-of-four ratio was lower at 3 min, 6 min, 9 min, 12 min and 15 min after reversal in the diabetic group than in the control group but the dif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 33 publications
1
10
0
Order By: Relevance
“…4,5,8 This fact can explain the delayed return of the neuromuscular function in aforementioned studies of Saitoh and colleagues. However, sugammadex effects by incapsulation of rocuronium molecules without any impact on the neuromuscular junction, thus we think that is the reason of why no difference occurred in terms of reversal times from neuromuscular blockade between diabetic and nondiabetic patients.…”
Section: Discussionmentioning
confidence: 90%
See 2 more Smart Citations
“…4,5,8 This fact can explain the delayed return of the neuromuscular function in aforementioned studies of Saitoh and colleagues. However, sugammadex effects by incapsulation of rocuronium molecules without any impact on the neuromuscular junction, thus we think that is the reason of why no difference occurred in terms of reversal times from neuromuscular blockade between diabetic and nondiabetic patients.…”
Section: Discussionmentioning
confidence: 90%
“…13 In other studies of the same author, the TOF ratio was lower at 3 min, 6 min, 9 min, 12 min and 15 min after administration of the reversal agent neostigmine in the diabetic group than in the control group, however the differences did not reach statistical significance. 8 The recovery of T1/control and TOF ratio were delayed in diabetic patients receiving anticholinesterase. 9 Times to return of T2, T3, T4 and a TOF ratio of 0.9 were significant longer in diabetic patients.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Some researchers demonstrated that recovery from the nondepolarizing neuromuscular agent, vecuronium, is delayed in diabetic patients compared with nondiabetic patients [26][27][28] because diabetic patients exhibit degeneration, demyelination, or axon loss in the motor nerve ending of the neuromuscular junction and infarction or atrophy in the skeletal muscle. It is known that volatile anesthetics such as sevoflurane or isoflurane enhance the action of neuromuscular relaxants, so that physicians must be aware of delayed recovery from the effects of nondepolarizing neuromuscular-blocking agents under volatile anesthetics in diabetic patients.…”
Section: Neuromuscular Agentsmentioning
confidence: 98%
“…studied. Saitoh [25] in 2004, noted that the number of diabetic patients with TOF ratio < 0.9 was significantly greater than non-diabetics 15 minutes after neostigmine administration. Considering the pathophysiological changes described above, if less Ach is released, the reversion provided with anticholinesterase drugs will be slower because it is a competition between the concentration of NMB and Ach.…”
Section: Nmb Monitoring In Diabetic Patientsmentioning
confidence: 99%